Use of Leaves Treated with Hydrogen Peroxide in Case-Building by Phylloicus spp. (Trichoptera: Calamoceratidae) - Vidovix, Thyago Augusto da Silva; Martins, Renato Tavares; Duarte, Cleber; Pes, Ana Maria Oliveira (EntomoBrasilis, 2013)
The objective of this study was to assess if larvae of Phylloicus spp. show any preference for leaves with or without microorganisms when building cases. Two experiments were realized at municipality of Presidente Figueiredo (Amazonas – Brazil), containing leaves treated with Hydrogen peroxide (H2O2), a compost that has an antimicrobial action, and another one with untreated leaves. In the first were observed the case-building by larvae of Phylloicus spp. And in the second was tested the preference by treated or untreated leaves. The larvae were monitored during 24 hours and to statistical analysis was used the t-test. Were not observed significant differences in the number of discs used by the larvae in the first experiment (p=0.24; t=-0.73) and no preference by type of leaf in the second experiment (p=0.41; t=0.23). Therefore, we do not recommend the use of hydrogen peroxide in studies that aim to eliminate microorganisms from decomposing leaves. Uso de Folhas Tratadas com Peróxido de Hidrogênio na Construção de Abrigos por Phylloicus spp. (Trichoptera: Calamoceratidae) Resumo. O objetivo deste estudo foi avaliar se larvas de Phylloicus spp. possuem preferência por folhas com ou sem micro-organismos para a construção de abrigos. Dois experimentos foram realizados no município de Presidente Figueiredo (Amazonas – Brasil), contendo folhas tratadas com peróxido de hidrogênio (H2O2), composto que possui ação antimicrobiana, e folhas não tratadas. No primeiro observaram-se a construção de abrigos pelas larvas de Phylloicus spp. e no segundo testou-se a preferência por folhas tratadas ou não tratadas. As larvas foram monitoradas durante 24 horas e para a análise estatística foi utilizado o teste-t. Não foram observadas diferenças significativas no número de discos usados pelas larvas no primeiro experimento (p=0,24; t=-0,73) e nem na preferência pelo tipo de folha no segundo experimento (p=0,41; t=0,23). Portanto, não recomendamos o uso do peróxido de hidrogênio em estudos realizados em laboratório que visem à eliminação de micro-organismos de folhas em decomposição.